Performativitas Humor dalam Interpretasi Qur’an: Kajian Symbolic Interactionism atas Tafsir Lisan Gus Baha’ - Amrulloh, Kholiq; Arifin, Muhammad Ikhwanul (Kuras Institute, 2025)
Qur’anic interpretation in contemporary Indonesia demonstrates a significant shift from the authority of written texts toward performative authority mediated by digital platforms. This study aims to analyze the performativity of humor in the Qur’anic interpretation of KH. Bahauddin Nursalim (Gus Baha’) using a symbolic interactionist framework. Employing a qualitative approach employing interactional analysis of video recordings and lecture transcriptions, this research examines how humor symbols are utilized to negotiate theological messages. The findings indicate that humor in Gus Baha’s tafsir is not merely a rhetorical element but an integral epistemic mode of religious meaning-making. Humor functions as a mechanism to break epistemic tension to create positive affective alignment, facilitating shared understanding, and enabling the vernacularization of revelation. Furthermore, this study confirms that humor serves as a strategy for negotiating religious authority, transforming traditional hierarchical models into an inclusive, humanist, and participatory authority.